Infrared heat shielding type rare earth hafnate-based composite ceramic coating material and preparation method thereof

By using spinel structure ceramics as a diffuse phase, modified rare earthyrite ceramic material, solving the problem of existing materials that are easily penetrated by infrared heat at high temperature at high temperature, and realized the infrared thermal shielding composite ceramic coating materials Low thermal and high -infrared thermal shielding performance has extended the working life of coating materials.

CN119330728AActive Publication Date: 2025-01-21HARBIN INST OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411468448.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-21
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The existing rare earth hafnate ceramic materials are easily penetrated by infrared heat radiation at high temperatures, resulting in direct radiation heating of metal substrates, making it difficult to protect the thermal barrier coating.

Method used

Use spinel structure ceramics as a scattered phase, modified greenite/flawed fluorite structure, a rare earthylite base ceramics to prepare a kind of infrared thermal shielding composite ceramic coating material. This material is prepared by fascinating sintering legal to ensure uniform distribution of diffuse phase and enhance the infrared thermal shielding performance of the material.

Benefits of technology

At the same time, it has low thermal guidance and high temperature stability, and has an infrared thermal shielding performance with ultra -low infrared and excellent infrared heat shielding, which prolongs the working life of coating materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330728A_ABST
    Figure CN119330728A_ABST
Patent Text Reader

Abstract

The invention discloses an infrared heat shielding type rare earth hafnate-based composite ceramic coating material and a preparation method thereof, and belongs to the technical field of thermal barrier coating materials. The invention aims to solve the problems that although an existing rare earth hafnate ceramic material mainly adopting a pyrochlore / defect fluorite structure has the advantages of low thermal conductivity and stable high-temperature phase, the rare earth hafnate ceramic material does not have a shielding effect on infrared thermal radiation, and a prepared thermal barrier coating can be penetrated by the infrared thermal radiation at high temperature, so that a metal substrate is directly radiated and heated, and the thermal barrier coating cannot be damaged. Therefore, the service life of the coating material is shortened. According to the invention, spinel structure ceramic with low infrared transmittance, high infrared emissivity and high infrared absorptivity is used as a dispersed phase to modify rare earth hafnate-based phase ceramic with a pyrochlore / defect fluorite structure, so that the infrared heat shielding type composite ceramic coating material with low heat conductivity, stable high-temperature phase and ultralow infrared transmittance is prepared; good application prospects are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal barrier coating materials, and in particular relates to an infrared heat shielding rare earth hafniumate-based composite ceramic coating material and a preparation method thereof. Background Art

[0002] With the rapid development of the aerospace industry, in the process of pursuing a higher thrust-to-weight ratio (about 12-15), high-temperature hot-end components of aircraft engines are also subjected to the test of extreme high-temperature environments, and their structural integrity is also facing unprecedented challenges. Therefore, it is urgent to develop thermal barrier coatings to reduce the surface temperature of high-temperature hot-end components. Traditional YSZ thermal barrier coating materials have a series of serious problems such as phase change failure, poor sintering resistance and excessive thermal conductivity. There is an urgent need to develop a new type of thermal barrier coating material with low thermal conductivity and good phase stability. Among the existing candidate materials for thermal barrier coatings, rare earth hafnium oxide ceramic materials based on pyrochlore / defective fluorite structure have the advantages of low thermal conductivity and high-temperature phase stability. They should be able to replace YSZ as a new generation of thermal barrier coating materials, but the inherent high transmittance of this material to infrared thermal radiation makes the thermal barrier coating prepared by it very easy to be penetrated by infrared thermal radiation at high temperatures, resulting in direct radiation heating of the metal substrate, which is difficult to play the protective role of the thermal barrier coating. Obviously, it is difficult for a single-component rare earth hafnium salt material to simultaneously meet the performance requirements of low thermal conductivity, resistance to thermal radiation penetration, and excellent phase stability. Therefore, the second phase composite strategy is often used to improve the comprehensive performance of the material. However, the second phase composite has the defect that it is difficult to take both thermal conductivity and thermo-optical properties into account. Therefore, how to improve its resistance to thermal radiation penetration without reducing the thermal insulation performance (low thermal conductivity) of the material has become the key to the problem. Summary of the invention

[0003] The purpose of the present invention is to solve the problem that the existing rare earth hafniumate ceramic materials mainly based on pyrochlore / defective fluorite structure have the advantages of low thermal conductivity and high-temperature phase stability, but have no shielding effect on infrared thermal radiation. The prepared thermal barrier coating will be penetrated by infrared thermal radiation at high temperature, resulting in direct radiation heating of the metal substrate, thereby reducing the working life of the coating material. An infrared heat shielding rare earth hafniumate-based composite ceramic coating material and a preparation method thereof are provided.

[0004] The present invention uses spinel structure ceramics with low infrared transmittance, high infrared emissivity and high infrared absorptivity as dispersed phase, modifies rare earth hafnium salt-based phase ceramics with pyrochlore / defective fluorite structure, and prepares an infrared heat shielding composite ceramic coating material with low thermal conductivity, high temperature phase stability and ultra-low infrared transmittance.

[0005] The base phase component of an infrared heat shielding rare earth hafniumate-based composite ceramic coating material is a rare earth hafniumate ceramic with a pyrochlore / defective fluorite structure having low thermal conductivity, high melting point, no phase change at high temperature and good high temperature thermal stability. The chemical formula is A 2 Hf 2 O 7 , wherein the A element is selected from the rare earth elements La, Nd, Sm, Eu, Gd, Y, Dy, Ho, Er or Yb; the dispersed phase component of the composite ceramic coating material is selected from the oxide ceramic of spinel structure with high infrared absorptivity, high infrared emissivity, low infrared transmittance and high melting point, and its chemical formula is AB 2 O 4 , wherein the A and B elements are both selected from Fe, Cr, Mn, Ni or Cu.

[0006] A method for preparing an infrared heat shielding rare earth hafniumate-based composite ceramic coating material is specifically completed by the following steps:

[0007] 1. Preparation of base phase ceramic powder by solid phase sintering method:

[0008] Weigh A 2 O 3 and HfO 2 , the weighed A 2 O 3 and HfO 2 Mixing evenly to obtain mixed powder; calcining and crushing the mixed powder to obtain base phase ceramic powder;

[0009] A described in step 1 2 O 3 The element A is selected from the rare earth elements La, Nd, Sm, Eu, Gd, Y, Dy, Ho, Er or Yb;

[0010] A described in step 1 2 O 3 and HfO 2 The molar ratio is 1:2;

[0011] 2. Preparation of dispersed phase ceramic powder by solid phase sintering method:

[0012] Weigh AO and B 2 O 3 , weigh AO and B 2 O 3 Mixing evenly to obtain mixed powder; calcining and crushing the mixed powder to obtain dispersed phase ceramic powder;

[0013] AO and B described in step 2 2 O 3 The molar ratio is 1:1;

[0014] A in the AO in step 2 is selected from Fe, Cr, Mn, Ni or Cu;

[0015] B described in step 2 2 O 3 wherein B is selected from Fe, Cr, Mn, Ni or Cu;

[0016] 3. Preparation of composite ceramic block materials:

[0017] ①, weighing the base phase ceramic powder and the dispersed phase ceramic powder, and mixing the weighed base phase ceramic powder and the dispersed phase ceramic powder evenly to obtain a mixed powder;

[0018] The molar fraction of the dispersed phase ceramic powder in the mixed powder described in step 3① is 5% to 30%;

[0019] ②. Press the mixed powder into sheets, and then cold isostatically press to obtain a green body; let the green body stand for a period of time to release the internal stress during the static pressing process, and then calcine and polish to obtain an infrared heat shielding rare earth hafnium salt-based composite ceramic coating material.

[0020] Principle of the present invention:

[0021] The present invention designs and prepares a composite material in which a functional ceramic dispersed phase is uniformly distributed in a base phase thermal barrier ceramic by solid phase sintering; wherein the infrared heat shielding performance of the composite ceramic material is regulated by using a dispersed phase with high infrared emissivity, and impurity energy levels are constructed by factors such as oxygen vacancies, narrow energy bands, and valence behavior of constituent elements in the dispersed phase structure, thereby enhancing the internal carrier concentration of the material and the transition ability of electrons after absorbing infrared radiation energy; and by controlling the size of the dispersed phase to be less than 5 μm and the molar fraction to be between 5 and 30%, the dispersed phase is enhanced. The optical backscattering between the interface of dispersed phase ceramics and matrix phase ceramics makes the thermal conductivity of the composite ceramic material less than 2W / (m·K) in the range of 25-800℃, the infrared emissivity at room temperature in the 2.5-14μm band is higher than 0.85, the infrared emissivity at 800℃ is higher than 0.65, the room temperature absorptivity in the 200-2500nm band is greater than 0.8, and the room temperature transmittance in the 400-2500nm band is less than 0.002; the composite material has both low thermal conductivity and excellent infrared heat shielding performance.

[0022] Advantages of the present invention:

[0023] 1. An infrared heat shielding rare earth hafnium salt-based composite ceramic coating material prepared by the present invention has a breakthrough in the problem of low infrared emissivity, high infrared transmittance, and transparency / translucency for infrared thermal radiation compared with the existing thermal barrier ceramic coating candidate materials based on pyrochlore / defective fluorite structure;

[0024] Second, the present invention is simple to operate, and the low thermal conductivity and high infrared heat shielding properties of the material can be achieved through solid phase sintering, and the prepared material has high density, good structure and strong stability, so that the infrared heat shielding rare earth hafnium salt-based composite ceramic coating material provided by the present invention has good application prospects;

[0025] 3. The infrared heat-shielding rare earth hafnium salt-based composite ceramic coating material prepared by the present invention has a thermal conductivity of less than 2W / (m·K) in the range of 25-800°C, a room-temperature infrared emissivity of higher than 0.85 in the 2.5-14μm band, an infrared emissivity of higher than 0.65 at 800°C, a room-temperature absorptivity of greater than 0.8 in the 200-2500nm band, and a room-temperature transmittance of less than 0.002 in the 400-2500nm band. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a comparison of the surface optical photographs of the infrared heat shielding rare earth hafniumate-based composite ceramic coating material prepared in Example 1 of the present invention and the thermal barrier ceramic single-phase material prepared in Comparative Example 1;

[0027] Figure 2 This is a SEM image of the infrared heat shielding rare earth hafniumate-based composite ceramic coating material prepared in Example 1 of the present invention;

[0028] Figure 3 XRD spectra of the infrared heat shielding rare earth hafnium salt-based composite ceramic coating material prepared in Example 1 of the present invention and the thermal barrier ceramic single-phase material prepared in Comparative Example 1;

[0029] Figure 4 This is a comparison chart of thermal conductivity of the infrared heat shielding rare earth hafniumate-based composite ceramic coating materials prepared in Examples 1-4 of the present invention and the single-phase ceramic material prepared in Comparative Example 1;

[0030] Figure 5 This is a comparison chart of thermal diffusion coefficients of the infrared heat shielding rare earth hafnium salt-based composite ceramic coating materials prepared in Examples 1-4 of the present invention and the single-phase ceramic material prepared in Comparative Example 1;

[0031] Figure 6 This is a comparison chart of average infrared emissivity of the infrared heat shielding rare earth hafnium salt-based composite ceramic coating materials prepared in Examples 1-4 of the present invention and the single-phase ceramic material prepared in Comparative Example 1;

[0032] Figure 7 The room temperature transmittance spectra of the infrared heat shielding rare earth hafnium salt-based composite ceramic coating materials prepared in Examples 1-4 of the present invention and the single-phase ceramic material prepared in Comparative Example 1;

[0033] Figure 8The room temperature absorptivity graphs of the infrared heat shielding rare earth hafnium salt-based composite ceramic coating materials prepared in Examples 1-4 of the present invention and the single-phase ceramic material prepared in Comparative Example 1 are shown. DETAILED DESCRIPTION

[0034] Specific implementation method 1: This implementation method is an infrared heat shielding rare earth hafnium salt-based composite ceramic coating material, the base phase component is a rare earth hafnium salt ceramic with a pyrochlore / defective fluorite structure having low thermal conductivity, high melting point, no phase change at high temperature and good high temperature thermal stability, and its chemical formula is A 2 Hf 2 O 7 , wherein the A element is selected from the rare earth elements La, Nd, Sm, Eu, Gd, Y, Dy, Ho, Er or Yb; the dispersed phase component of the composite ceramic coating material is selected from the oxide ceramic of spinel structure with high infrared absorptivity, high infrared emissivity, low infrared transmittance and high melting point, and its chemical formula is AB 2 O 4 , wherein the A and B elements are both selected from Fe, Cr, Mn, Ni or Cu.

[0035] Specific embodiment 2: This embodiment differs from the specific embodiment 1 in that: a method for preparing an infrared heat shielding rare earth hafniumate-based composite ceramic coating material is specifically completed in the following steps:

[0036] 1. Preparation of base phase ceramic powder by solid phase sintering method:

[0037] Weigh A 2 O 3 and HfO 2 , the weighed A 2 O 3 and HfO 2 Mixing evenly to obtain mixed powder; calcining and crushing the mixed powder to obtain base phase ceramic powder;

[0038] A described in step 1 2 O 3 The element A is selected from the rare earth elements La, Nd, Sm, Eu, Gd, Y, Dy, Ho, Er or Yb;

[0039] A described in step 1 2 O 3 and HfO 2 The molar ratio is 1:2;

[0040] 2. Preparation of dispersed phase ceramic powder by solid phase sintering method:

[0041] Weigh AO and B 2 O 3 , weigh AO and B 2 O3 Mixing evenly to obtain mixed powder; calcining and crushing the mixed powder to obtain dispersed phase ceramic powder;

[0042] AO and B described in step 2 2 O 3 The molar ratio is 1:1;

[0043] A in the AO in step 2 is selected from Fe, Cr, Mn, Ni or Cu;

[0044] B described in step 2 2 O 3 wherein B is selected from Fe, Cr, Mn, Ni or Cu;

[0045] 3. Preparation of composite ceramic block materials:

[0046] ①, weighing the base phase ceramic powder and the dispersed phase ceramic powder, and mixing the weighed base phase ceramic powder and the dispersed phase ceramic powder evenly to obtain a mixed powder;

[0047] The molar fraction of the dispersed phase ceramic powder in the mixed powder described in step 3① is 5% to 30%;

[0048] ②, the mixed powder is pressed into sheets, and then cold isostatically pressed to obtain a green body; the green body is left to stand for a period of time to release the internal stress during the static pressing process, and then calcined and polished to obtain an infrared heat shielding rare earth hafnium salt-based composite ceramic coating material. The other steps are the same as the first embodiment.

[0049] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the mixing method described in step one is: 2 O 3 , HfO 2 , anhydrous ethanol and zirconium oxide grinding balls are put into a ball mill, and then ball milled for 20h to 24h, and then dried and sieved to obtain a mixed powder; the A 2 O 3 and HfO 2 The mass ratio of the total mass of the raw material to the anhydrous ethanol and the zirconium oxide is 1:0.2:4; the rotation speed of the ball mill is 200r / min to 600r / min, and the ball milling time is 12h to 24h; the drying temperature is 80℃ to 120℃, and the drying time is 12h to 24h; the screening method is: passing through a 150-mesh to 300-mesh sieve. The other steps are the same as those in the first or second specific implementation.

[0050] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the calcination temperature in step 1 is 1300°C to 1500°C, and the calcination time is 6h to 12h; the crushing in step 1 is: crushing with a wall breaker or mortar, and sieving with a 300-mesh screen. The other steps are the same as those in specific embodiments 1 to 3.

[0051] Specific implementation method 5: This implementation method is different from specific implementation methods 1 to 4 in that the mixing method described in step 2 is: AO, B 2 O 3 , anhydrous ethanol and zirconium oxide grinding balls are put into a ball mill, and then ball milled for 20h to 24h, and then dried and sieved to obtain a mixed powder; the AO and B 2 O 3 The mass ratio of the total mass of the raw material to the anhydrous ethanol and the zirconium oxide is 1:0.2:4; the speed of the ball mill is 200r / min to 600r / min, and the ball milling time is 12h to 24h; the drying temperature is 80℃ to 120℃, and the drying time is 12h to 24h; the screening method is: passing through a 150-mesh to 300-mesh sieve. The other steps are the same as those in the first to fourth embodiments.

[0052] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: the calcination temperature in step 2 is 1200°C to 1400°C, and the calcination time is 3h to 8h; the crushing in step 2 is: crushing with a wall breaker or mortar, and sieving with a 300-mesh screen. The other steps are the same as those in specific embodiments 1 to 5.

[0053] Specific implementation seven: This implementation is different from specific implementations one to six in that: the mixing method described in step three ① is: put the base phase ceramic powder, dispersed phase ceramic powder, anhydrous ethanol and zirconium oxide grinding balls into a ball mill, then ball mill for 20h to 24h, dry, and sieve to obtain a mixed powder; the total mass ratio of the base phase ceramic powder and dispersed phase ceramic powder to anhydrous ethanol and zirconium oxide is 1:0.2:4; the speed of the ball mill is 200r / min to 600r / min, and the ball milling time is 12-24h; the drying temperature is 80℃ to 120℃, and the drying time is 12h to 24h; the sieving method is: sieve through a 150-mesh to 300-mesh sieve. The other steps are the same as specific implementations one to six.

[0054] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: the process of pressing into tablets described in step three ② is: holding the pressure at 8MPa to 15MPa for 1min to 5min; the process of cold isostatic pressing described in step three ② is: increasing the pressure to 180MPa to 220MPa, holding the pressure at 180MPa to 220MPa for 3min to 8min, and then reducing the pressure to 0MPa; the time for increasing and reducing the pressure is 150s to 200s; the time for the green body to stand still described in step three ② is 8h to 16h. The other steps are the same as those of specific embodiments one to seven.

[0055] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the calcination temperature in step 3 ② is 1500°C to 1600°C, and the calcination time is 8h to 12h; the polishing in step 3 ② is to use sandpaper to grind the surface of the block ceramic to smoothness, wherein the sandpaper mesh is 80#, 240#, 400#, 800#, 1500#, 2000#. The other steps are the same as those in specific embodiments 1 to 8.

[0056] Specific embodiment 10: The difference between this embodiment and specific embodiments 1 to 9 is that the performance index of the infrared heat shielding rare earth hafnium salt-based composite ceramic coating material is: when the thickness is 1mm, the performance index of the test band of the normal temperature transmittance is 400-2500nm, which is lower than 0.002; when the thickness is 2mm, the performance index of the test band of the normal temperature absorptivity is 200-2500nm, which is higher than 0.8; when the thickness is 2mm, the test band of the infrared emissivity is 2.5-14μm, the test temperature is 25-800℃, the performance index is higher than 0.85 at room temperature and higher than 0.65 at high temperature; when the thickness is 2mm, the test temperature of the thermal conductivity is 25-800℃, and the performance index is less than 2W / (m·K). The other steps are the same as specific embodiments 1 to 9.

[0057] The following examples are used to verify the beneficial effects of the present invention:

[0058] Example 1: An infrared heat shielding rare earth hafnium salt-based composite ceramic coating material (85 mol% -La 2 Hf 2 O 7 / 15mol%-NiFe 2 O 4 ), which is specifically completed by the following steps:

[0059] 1. Preparation of base phase ceramic powder by solid phase sintering method:

[0060] Weigh La 2 O 3 and HfO 2 , the weighed La2 O 3 and HfO 2 The mixed powder was calcined at 1400°C for 8 hours and crushed to obtain a base phase ceramic powder (La 2 Hf 2 O 7 );

[0061] La described in step 1 2 O 3 and HfO 2 The molar ratio is 1:2;

[0062] The mixing method described in step 1 is: La 2 O 3 , HfO 2 , anhydrous ethanol and zirconium oxide grinding balls were put into a ball mill, and then ball milled at a speed of 400 r / min for 24 h, and then dried at 90° C. for 12 h, and passed through a 300-mesh sieve to obtain a mixed powder;

[0063] The La 2 O 3 and HfO 2 The mass ratio of the total mass of anhydrous ethanol and zirconium oxide is 1:0.2:4;

[0064] The crushing in step 1 is: crushing with a wall breaker and sieving with a 300-mesh sieve;

[0065] 2. Preparation of dispersed phase ceramic powder by solid phase sintering method:

[0066] Weigh NiO and Fe 2 O 3 , weigh NiO and Fe 2 O 3 The mixed powder was calcined at 1200°C for 3 hours and crushed to obtain a dispersed phase ceramic powder (NiFe 2 O 4 );

[0067] NiO and Fe described in step 2 2 O 3 The molar ratio is 1:1;

[0068] The mixing method described in step 2 is: NiO, Fe 2 O 3 , anhydrous ethanol and zirconium oxide grinding balls were put into a ball mill, and then ball milled at a speed of 400 r / min for 24 h, and then dried at 90° C. for 12 h, and passed through a 300-mesh sieve to obtain a mixed powder;

[0069] The NiO and Fe2 O 3 The mass ratio of the total mass of anhydrous ethanol and zirconium oxide is 1:0.2:4;

[0070] The crushing in step 2 is: crushing with a wall breaking machine and sieving with a 300-mesh sieve;

[0071] 3. Preparation of composite ceramic block materials:

[0072] ①, weigh the base phase ceramic powder (La 2 Hf 2 O 7 ) and dispersed phase ceramic powder (NiFe 2 O 4 ), mixing the weighed base phase ceramic powder and dispersed phase ceramic powder evenly to obtain a mixed powder;

[0073] The base phase ceramic powder (La 2 Hf 2 O 7 ) and dispersed phase ceramic powder (NiFe 2 O 4 ) has a molar ratio of 85:15;

[0074] The mixing method described in step 3① is: putting the base phase ceramic powder, the dispersed phase ceramic powder, anhydrous ethanol and zirconium oxide grinding balls into a ball mill, then ball milling at a speed of 400r / min for 24h, then drying at 90°C for 12h, and passing through a 300-mesh sieve to obtain a mixed powder;

[0075] The mass ratio of the total mass of the matrix ceramic powder and the dispersed phase ceramic powder to the anhydrous ethanol and zirconium oxide is 1:0.2:4;

[0076] ②, the mixed powder was pressed into a sheet at 10MPa for 3 minutes, and then cold isostatically pressed to obtain a green body; the green body was left to stand for 12 hours to release the internal stress during the static pressing process, and then calcined at 1550°C for 10 hours, and finally polished to obtain an infrared heat shielding rare earth hafnium salt-based composite ceramic coating material;

[0077] The cold isostatic pressing process described in step 3② is: increasing the pressure to 200 MPa, maintaining the pressure at 200 MPa for 5 minutes, and then reducing the pressure to 0 MPa; the time for increasing and reducing the pressure is 180 seconds;

[0078] The polishing described in step 3② is to use sandpaper to grind the surface of the block ceramic until it is smooth, wherein the grit of the sandpaper is 80#, 240#, 400#, 800#, and 1500#.

[0079] Example 2: The difference between this example and example 1 is that the base phase ceramic powder (La2 Hf 2 O 7 ) and dispersed phase ceramic powder (NiFe 2 O 4 ) is 70:30, and the obtained product is an infrared heat shielding rare earth hafnium salt-based composite ceramic coating material (70mol%-La 2 Hf 2 O 7 / 30mol%-NiFe 2 O 4 ). Other steps and parameters are the same as those in Example 1.

[0080] Example 3: An infrared heat shielding rare earth hafnium salt-based composite ceramic coating material (85 mol% -Gd 2 Hf 2 O 7 / 15mol%-NiFe 2 O 4 ), which is specifically completed by the following steps:

[0081] 1. Preparation of base phase ceramic powder by solid phase sintering method:

[0082] Weigh Gd 2 O 3 and HfO 2 , the Gd 2 O 3 and HfO 2 The mixed powder was calcined at 1400°C for 8 h and crushed to obtain a base phase ceramic powder (Gd 2 Hf 2 O 7 );

[0083] Gd as described in step 1 2 O 3 and HfO 2 The molar ratio is 1:2;

[0084] The mixing method described in step 1 is: Gd 2 O 3 , HfO 2 , anhydrous ethanol and zirconium oxide grinding balls were put into a ball mill, and then ball milled at a speed of 400 r / min for 24 h, and then dried at 90° C. for 12 h, and passed through a 300-mesh sieve to obtain a mixed powder;

[0085] The Gd 2 O 3 and HfO 2 The mass ratio of the total mass of anhydrous ethanol and zirconium oxide is 1:0.2:4;

[0086] The crushing in step 1 is: crushing with a wall breaker and sieving with a 300-mesh sieve;

[0087] 2. Preparation of dispersed phase ceramic powder by solid phase sintering method:

[0088] Weigh NiO and Fe 2 O 3 , weigh NiO and Fe 2 O 3 The mixed powder was calcined at 1200°C for 3 hours and crushed to obtain a dispersed phase ceramic powder (NiFe 2 O 4 );

[0089] NiO and Fe described in step 2 2 O 3 The molar ratio is 1:1;

[0090] The mixing method described in step 2 is: NiO, Fe 2 O 3 , anhydrous ethanol and zirconium oxide grinding balls were put into a ball mill, and then ball milled at a speed of 400 r / min for 24 h, and then dried at 90° C. for 12 h, and passed through a 300-mesh sieve to obtain a mixed powder;

[0091] The NiO and Fe 2 O 3 The mass ratio of the total mass of anhydrous ethanol and zirconium oxide is 1:0.2:4;

[0092] The crushing in step 2 is: crushing with a wall breaking machine and sieving with a 300-mesh sieve;

[0093] 3. Preparation of composite ceramic block materials:

[0094] ①, weigh the base phase ceramic powder (Gd 2 Hf 2 O 7 ) and dispersed phase ceramic powder (NiFe 2 O 4 ), mixing the weighed base phase ceramic powder and dispersed phase ceramic powder evenly to obtain a mixed powder;

[0095] The base phase ceramic powder (Gd 2 Hf 2 O 7 ) and dispersed phase ceramic powder (NiFe 2 O 4 ) has a molar ratio of 85:15;

[0096] The mixing method described in step 3① is: putting the base phase ceramic powder, the dispersed phase ceramic powder, anhydrous ethanol and zirconium oxide grinding balls into a ball mill, then ball milling at a speed of 400r / min for 24h, then drying at 90°C for 12h, and passing through a 300-mesh sieve to obtain a mixed powder;

[0097] The mass ratio of the total mass of the matrix ceramic powder and the dispersed phase ceramic powder to the anhydrous ethanol and zirconium oxide is 1:0.2:4;

[0098] ②, the mixed powder was pressed into a sheet at 10MPa for 3 minutes, and then cold isostatically pressed to obtain a green body; the green body was left to stand for 12 hours to release the internal stress during the static pressing process, and then calcined at 1550°C for 10 hours, and finally polished to obtain an infrared heat shielding rare earth hafnium salt-based composite ceramic coating material;

[0099] The cold isostatic pressing process described in step 3② is: increasing the pressure to 200 MPa, maintaining the pressure at 200 MPa for 5 minutes, and then reducing the pressure to 0 MPa; the time for increasing and reducing the pressure is 180 seconds;

[0100] The polishing described in step 3② is to use sandpaper to grind the surface of the block ceramic until it is smooth, wherein the grit of the sandpaper is 80#, 240#, 400#, 800#, and 1500#.

[0101] Example 4: An infrared heat shielding rare earth hafnium salt-based composite ceramic coating material (85 mol% -La 2 Hf 2 O 7 / 15mol%-NiCr 2 O 4 ), which is specifically completed by the following steps:

[0102] 1. Preparation of base phase ceramic powder by solid phase sintering method:

[0103] Weigh La 2 O 3 and HfO 2 , the weighed La 2 O 3 and HfO 2 The mixed powder was calcined at 1400°C for 8 hours and crushed to obtain a base phase ceramic powder (La 2 Hf 2 O 7 );

[0104] La described in step 1 2 O 3 and HfO 2 The molar ratio is 1:2;

[0105] The mixing method described in step 1 is: La 2 O 3 , HfO 2 , anhydrous ethanol and zirconium oxide grinding balls were put into a ball mill, and then ball milled at a speed of 400 r / min for 24 h, and then dried at 90° C. for 12 h, and passed through a 300-mesh sieve to obtain a mixed powder;

[0106] The La 2 O 3 and HfO 2 The mass ratio of the total mass of anhydrous ethanol and zirconium oxide is 1:0.2:4;

[0107] The crushing in step 1 is: crushing with a wall breaker and sieving with a 300-mesh sieve;

[0108] 2. Preparation of dispersed phase ceramic powder by solid phase sintering method:

[0109] Weigh NiO and Cr 2 O 3 , weigh NiO and Cr 2 O 3 The mixed powder was calcined at 1200°C for 3h and crushed to obtain a dispersed phase ceramic powder (NiCr 2 O 4 );

[0110] NiO and Cr as described in step 2 2 O 3 The molar ratio is 1:1;

[0111] The mixing method described in step 2 is: NiO, Cr 2 O 3 , anhydrous ethanol and zirconium oxide grinding balls were put into a ball mill, and then ball milled at a speed of 400 r / min for 24 h, and then dried at 90° C. for 12 h, and passed through a 300-mesh sieve to obtain a mixed powder;

[0112] The NiO and Cr 2 O 3 The mass ratio of the total mass of anhydrous ethanol and zirconium oxide is 1:0.2:4;

[0113] The crushing in step 2 is: crushing with a wall breaking machine and sieving with a 300-mesh sieve;

[0114] 3. Preparation of composite ceramic block materials:

[0115] ①, weigh the base phase ceramic powder (La 2 Hf 2 O 7 ) and dispersed phase ceramic powder (NiCr2 O 4 ), mixing the weighed base phase ceramic powder and dispersed phase ceramic powder evenly to obtain a mixed powder;

[0116] The base phase ceramic powder (La 2 Hf 2 O 7 ) and dispersed phase ceramic powder (NiCr 2 O 4 ) has a molar ratio of 85:15;

[0117] The mixing method described in step 3① is: putting the base phase ceramic powder, the dispersed phase ceramic powder, anhydrous ethanol and zirconium oxide grinding balls into a ball mill, then ball milling at a speed of 400r / min for 24h, then drying at 90°C for 12h, and passing through a 300-mesh sieve to obtain a mixed powder;

[0118] The mass ratio of the total mass of the matrix ceramic powder and the dispersed phase ceramic powder to the anhydrous ethanol and zirconium oxide is 1:0.2:4;

[0119] ②, the mixed powder was pressed into a sheet at 10MPa for 3 minutes, and then cold isostatically pressed to obtain a green body; the green body was left to stand for 12 hours to release the internal stress during the static pressing process, and then calcined at 1550°C for 10 hours, and finally polished to obtain an infrared heat shielding rare earth hafnium salt-based composite ceramic coating material;

[0120] The cold isostatic pressing process described in step 3② is: increasing the pressure to 200 MPa, maintaining the pressure at 200 MPa for 5 minutes, and then reducing the pressure to 0 MPa; the time for increasing and reducing the pressure is 180 seconds;

[0121] The polishing described in step 3② is to use sandpaper to grind the surface of the block ceramic until it is smooth, wherein the grit of the sandpaper is 80#, 240#, 400#, 800#, and 1500#.

[0122] Comparative Example 1: La 2 Hf 2 O 7 The preparation method of single-phase ceramic material is completed according to the following steps:

[0123] 1. Preparation of La 2 Hf 2 O 7 Ceramic powder:

[0124] Weigh La 2 O 3 and HfO 2 , the weighed La 2 O 3 and HfO 2Mix well to obtain mixed powder; calcine the mixed powder at 1400℃ for 8h and crush it to obtain La 2 Hf 2 O 7 Ceramic powder;

[0125] La described in step 1 2 O 3 and HfO 2 The molar ratio is 1:2;

[0126] The mixing method described in step 1 is: La 2 O 3 , HfO 2 , anhydrous ethanol and zirconium oxide grinding balls were put into a ball mill, and then ball milled at a speed of 400 r / min for 24 h, and then dried at 90° C. for 12 h, and passed through a 300-mesh sieve to obtain a mixed powder;

[0127] The La 2 O 3 and HfO 2 The mass ratio of the total mass of anhydrous ethanol and zirconium oxide is 1:0.2:4;

[0128] The crushing in step 1 is: crushing with a wall breaker and sieving with a 300-mesh sieve;

[0129] 2. Preparation of ceramic block materials:

[0130] To La 2 Hf 2 O 7 The ceramic powder is ball-milled, dried, sieved, pressed into sheets, cold isostatically pressed, calcined and polished to obtain La 2 Hf 2 O 7 Single-phase ceramic materials;

[0131] The ball milling method described in step 2① is: La 2 Hf 2 O 7 Ceramic powder, anhydrous ethanol and zirconium oxide grinding balls are placed in a ball mill, and then ball milled at a speed of 400 r / min for 24 hours; the La 2 Hf 2 O 7 The mass ratio of ceramic powder, anhydrous ethanol and zirconium oxide is 1:0.2:4;

[0132] The drying in step 2① is: drying at 90°C for 12h; the sieving is: passing through a 300-mesh sieve;

[0133] The pressing into tablets in step 2① is performed by pressing into tablets at a pressure of 10 MPa for 3 minutes;

[0134] The cold isostatic pressing described in step 2① is as follows: increasing the pressure to 200 MPa, maintaining the pressure at 200 MPa for 5 minutes, and then reducing the pressure to 0 MPa; the time for increasing and reducing the pressure is 180 seconds to obtain a green body; the green body is left to stand for 12 hours to release the internal stress during the static pressing process;

[0135] The calcination in step 2① is: calcining at 1550°C for 10 hours;

[0136] The polishing described in step 2① is to use sandpaper to grind the surface of the block ceramic until it is smooth, wherein the grit of the sandpaper is 80#, 240#, 400#, 800#, and 1500#.

[0137] Figure 1 This is a comparison of the surface optical photographs of the infrared heat shielding rare earth hafniumate-based composite ceramic coating material prepared in Example 1 of the present invention and the thermal barrier ceramic single-phase material prepared in Comparative Example 1;

[0138] from Figure 1 It can be seen that the prepared infrared heat shielding rare earth hafnium salt-based composite ceramic coating material has good density, smooth surface, no obvious holes and cracks; and the composite material has obvious color difference from the single-phase material on a macro scale.

[0139] Figure 2 This is a SEM image of the infrared heat shielding rare earth hafniumate-based composite ceramic coating material prepared in Example 1 of the present invention;

[0140] from Figure 2 It can be seen that Example 1 successfully prepared NiFe 2 O 4 Diffuse distribution in La 2 Hf 2 O 7 Composite ceramic materials, and dispersed phase ceramic NiFe 2 O 4 The grain size is within 5μm, and the base phase ceramic La 2 Hf 2 O 7 The grain size is within 15μm.

[0141] Figure 3 XRD spectra of the infrared heat shielding rare earth hafnium salt-based composite ceramic coating material prepared in Example 1 of the present invention and the thermal barrier ceramic single-phase material prepared in Comparative Example 1;

[0142] from Figure 3 It can be seen that the infrared heat shielding rare earth hafnium salt-based composite ceramic coating material prepared in Example 1 contains La 2 Hf 2 O7 and NiFe 2 O 4 Two phases, indicating that La 2 Hf 2 O 7 and NiFe 2 O 4 They can coexist in a multiphase structure and will not dissolve to form a single-phase material. At the same time, the optical scattering of the multiphase interface also provides conditions for improving the emissivity of the composite material.

[0143] Figure 4 This is a comparison chart of thermal conductivity of the infrared heat shielding rare earth hafniumate-based composite ceramic coating materials prepared in Examples 1-4 of the present invention and the single-phase ceramic material prepared in Comparative Example 1;

[0144] Figure 5 This is a comparison chart of thermal diffusion coefficients of the infrared heat shielding rare earth hafnium salt-based composite ceramic coating materials prepared in Examples 1-4 of the present invention and the single-phase ceramic material prepared in Comparative Example 1;

[0145] The thermal conductivity and thermal diffusivity of the prepared sample materials were measured using an LFA457 laser thermal conductivity meter. It can be seen that the room temperature thermal conductivity and thermal diffusivity of the composite materials prepared in Examples 1-4 are significantly reduced, among which the reduction in Example 1 is the most obvious, with a room temperature thermal conductivity of 1.89 W / (m·K), a high temperature thermal conductivity of 1.55 W / (m·K), and a room temperature thermal diffusivity of 0.87 mm 2 ·s -1 , high temperature thermal diffusion coefficient is only 0.52mm 2 ·s -1 , which lays the foundation for the composite material to have excellent infrared heat shielding effect.

[0146] Figure 6 This is a comparison chart of average infrared emissivity of the infrared heat shielding rare earth hafnium salt-based composite ceramic coating materials prepared in Examples 1-4 of the present invention and the single-phase ceramic material prepared in Comparative Example 1;

[0147] The room temperature and high temperature infrared emissivity of the prepared sample materials were measured using a Bruker VERTEX 70 Fourier transform infrared spectrometer and a high temperature emissivity tester made by the research team. It can be seen that the room temperature infrared emissivity of the composite materials prepared in Examples 1-4 in the 2.5-14 μm band is higher than 0.8, and the high temperature emissivity is higher than 0.6, which is significantly higher than the single-phase material prepared in Comparative Example 1, laying the foundation for the composite materials to have excellent infrared heat shielding effect.

[0148] Figure 7The room temperature transmittance spectra of the infrared heat shielding rare earth hafnium salt-based composite ceramic coating materials prepared in Examples 1-4 of the present invention and the single-phase ceramic material prepared in Comparative Example 1;

[0149] The room temperature transmittance of the prepared sample materials was measured using a PerkinElmer LAMBDA 1050 spectrophotometer. It can be seen that the room temperature transmittance of the composite materials prepared in Examples 1-4 in the 400-2500 nm band is lower than 0.002, which is significantly lower than the single-phase material prepared in Comparative Example 1, thereby proving that the composite ceramic material prepared in this example has excellent infrared heat shielding effect.

[0150] Figure 8 The room temperature absorptivity spectra of the infrared heat shielding rare earth hafnium salt-based composite ceramic coating materials prepared in Examples 1-4 of the present invention and the single-phase ceramic material prepared in Comparative Example 1;

[0151] The room temperature absorptivity of the prepared sample materials was measured using a PerkinElmer LAMBDA 750 spectrophotometer. It can be seen that the room temperature absorptivity of the composite materials prepared in Examples 1-4 in the 200-2500nm band was higher than 0.8, which was significantly higher than the single-phase material prepared in Comparative Example 1, laying the foundation for the composite materials to have excellent infrared heat shielding effect.

Claims

1. An infrared heat shielding rare earth hafnium salt-based composite ceramic coating material, characterized in that The base phase component of the composite ceramic coating material is a rare earth hafnium oxide ceramic with a pyrochlore / defective fluorite structure having low thermal conductivity, high melting point, no phase change at high temperature and good high temperature thermal stability, and its chemical formula is A2Hf2O7, wherein the A element is selected from rare earth elements La, Nd, Sm, Eu, Gd, Y, Dy, Ho, Er or Yb; the dispersed phase component of the composite ceramic coating material is an oxide ceramic with a spinel structure having high infrared absorptivity, high infrared emissivity, low infrared transmittance and high melting point, and its chemical formula is AB2O4, wherein the A and B elements are both selected from Fe, Cr, Mn, Ni or Cu.

2. The method for preparing an infrared heat shielding rare earth hafniumate-based composite ceramic coating material according to claim 1, characterized in that The preparation method is specifically completed according to the following steps:

1. Preparation of base phase ceramic powder by solid phase sintering method: Weighing A2O3 and HfO2, and mixing the weighed A2O3 and HfO2 uniformly to obtain a mixed powder; calcining and crushing the mixed powder to obtain a base phase ceramic powder; The A element in the A2O3 described in step 1 is selected from the rare earth elements La, Nd, Sm, Eu, Gd, Y, Dy, Ho, Er or Yb; The molar ratio of A2O3 and HfO2 described in step 1 is 1:2; 2. Preparation of dispersed phase ceramic powder by solid phase sintering method: Weighing AO and B2O3, and mixing the weighed AO and B2O3 uniformly to obtain a mixed powder; calcining and crushing the mixed powder to obtain a dispersed phase ceramic powder; The molar ratio of AO and B2O3 described in step 2 is 1:1; A in the AO in step 2 is selected from Fe, Cr, Mn, Ni or Cu; In the B2O3 described in step 2, B is selected from Fe, Cr, Mn, Ni or Cu; 3. Preparation of composite ceramic block materials: ①, weighing the base phase ceramic powder and the dispersed phase ceramic powder, and mixing the weighed base phase ceramic powder and the dispersed phase ceramic powder evenly to obtain a mixed powder; The molar fraction of the dispersed phase ceramic powder in the mixed powder described in step 3① is 5% to 30%; ② Press the mixed powder into sheets, and then cold isostatically press to obtain a green body; let the green body stand for a period of time to release the internal stress during the static pressing process, and then calcine and polish to obtain an infrared heat shielding rare earth hafnium salt-based composite ceramic coating material.

3. The method for preparing an infrared heat shielding rare earth hafniumate-based composite ceramic coating material according to claim 2, characterized in that The mixing method described in step one is: putting A2O3, HfO2, anhydrous ethanol and zirconium oxide grinding balls into a ball mill, then ball milling for 20h to 24h, drying, sieving, and obtaining a mixed powder; the mass ratio of the total mass of A2O3 and HfO2 to anhydrous ethanol and zirconium oxide is 1:0.2:4; the rotation speed of the ball mill is 200r / min to 600r / min, and the ball milling time is 12h to 24h; the drying temperature is 80℃ to 120℃, and the drying time is 12h to 24h; the screening method is: passing through a 150-mesh to 300-mesh sieve.

4. The method for preparing an infrared heat shielding rare earth hafniumate-based composite ceramic coating material according to claim 2, characterized in that The calcination temperature in step one is 1300° C. to 1500° C., and the calcination time is 6 h to 12 h. The crushing in step one is: crushing with a wall breaker or a mortar, and sieving with a 300-mesh sieve.

5. The method for preparing an infrared heat shielding rare earth hafniumate-based composite ceramic coating material according to claim 2, characterized in that The mixing method described in step 2 is: putting AO, B2O3, anhydrous ethanol and zirconium oxide grinding balls into a ball mill, then ball milling for 20h to 24h, drying, sieving, and obtaining a mixed powder; the mass ratio of the total mass of AO and B2O3 to anhydrous ethanol and zirconium oxide is 1:0.2:4; the rotation speed of the ball mill is 200r / min to 600r / min, and the ball milling time is 12h to 24h; the drying temperature is 80℃ to 120℃, and the drying time is 12h to 24h; the screening method is: passing through a 150-mesh to 300-mesh sieve.

6. The method for preparing an infrared heat shielding rare earth hafniumate-based composite ceramic coating material according to claim 2, characterized in that The calcination temperature in step 2 is 1200° C. to 1400° C., and the calcination time is 3 h to 8 h. The crushing in step 2 is performed by using a wall breaker or a mortar, and sieving using a 300-mesh screen.

7. The method for preparing an infrared heat shielding rare earth hafniumate-based composite ceramic coating material according to claim 2, characterized in that The mixing method described in step three ① is: putting the base phase ceramic powder, the dispersed phase ceramic powder, anhydrous ethanol and zirconium oxide grinding balls into a ball mill, and then ball milling for 20h~24h, and then drying and sieving to obtain a mixed powder; the total mass ratio of the base phase ceramic powder and the dispersed phase ceramic powder to the mass ratio of anhydrous ethanol and zirconium oxide is 1:0.2:4; the rotation speed of the ball mill is 200r / min~600r / min, and the ball milling time is 12-24h; the drying temperature is 80℃~120℃, and the drying time is 12h~24h; the screening method is: passing through a 150-mesh sieve.

8. The method for preparing an infrared heat shielding rare earth hafniumate-based composite ceramic coating material according to claim 2, characterized in that The process of pressing into tablets described in step 3② is: maintaining the pressure at 8MPa~15MPa for 1min~5min; the process of cold isostatic pressing described in step 3② is: increasing the pressure to 180MPa~220MPa, maintaining the pressure at 180MPa~220MPa for 3min~8min, and then reducing the pressure to 0MPa; the time for increasing and reducing the pressure is 150s~200s; the time for the green body described in step 3② is 8h~16h.

9. The method for preparing an infrared heat shielding rare earth hafniumate-based composite ceramic coating material according to claim 2, characterized in that The calcination temperature described in step three ② is 1500℃~1600℃, and the calcination time is 8h~12h; the polishing described in step three ② is to use sandpaper to grind the surface of the block ceramic until it is smooth, and the sandpaper mesh number is 80#, 240#, 400#, 800#, 1500#, 2000#.

10. The method for preparing an infrared heat shielding rare earth hafniumate-based composite ceramic coating material according to claim 2, characterized in that The performance indicators of the infrared heat shielding rare earth hafnium salt-based composite ceramic coating material are as follows: when the thickness is 1 mm and the test band of the normal temperature transmittance is 400-2500 nm, the performance indicator is lower than 0.002; when the thickness is 2 mm and the test band of the normal temperature absorptivity is 200-2500 nm, the performance indicator is higher than 0.8; when the thickness is 2 mm, the test band of the infrared emissivity is 2.5-14 μm, the test temperature is 25-800° C., the performance indicator is higher than 0.85 at normal temperature and higher than 0.65 at high temperature; when the thickness is 2 mm and the test temperature of the thermal conductivity is 25-800° C., the performance indicator is less than 2 W / (m·K).

Citation Information

Patent Citations

  • Preparation method of high-toughness / low-thermal-conductivity / thermal radiation penetration resistance integrated thermal barrier ceramic coating

    CN116377373A

  • Rare earth zirconate high-entropy ceramic and preparation method thereof

    CN116874298A

  • Multi-principal-element rare earth cerate ceramic material based on passive radiation cooling

    CN118047611A

  • High-entropy rare earth hafnate ceramic coating material and preparation method thereof

    CN118084489A

  • Pyrochlore / defect fluorite zirconates

    US20230257595A1